Randomised clinical trial: otilonium bromide improves frequency of abdominal pain, severity of distention and time to relapse in patients with irritable bowel syndrome - (:unkn) unknown (WILEY-BLACKWELL, 2011)
Background Otilonium bromide (OB) is a spasmolytic agent that blocks L-Type Calcium channels in human colonic smooth muscle. Aim To study the efficacy of OB in symptom control in irritable bowel syndrome (IBS). Methods A total of 356 patients (46.16 +/- 19 years, 71% female) with IBS participated in a double-blind, randomised, parallel placebo-controlled phase IV study. OB (40 mg t.d.s.) or placebo was administered for 15 weeks, and follow-up was extended 10 additional weeks. Results Otilonium bromide (n = 179) and placebo (n = 177) groups had comparable demographics, symptom severity and IBS subtype. Both OB and placebo reduced abdominal pain and IBS symptoms. The effect of OB was significantly greater than placebo in the reduction of weekly frequency of episodes of abdominal pain at the end of treatment period (primary endpoint, -0.90 +/- 0.88 vs. -0.65 +/- 0.91, P = 0.03), reduction of abdominal bloating ( -1.2 +/- 1.2 vs. -0.9 +/- 1.1, P = 0.02) and global efficacy by patient assessment (1.3 +/- 1.1 vs. 1.0 +/- 1.1, P = 0.047). Intensity of abdominal pain, proportion of patient responders, safety and quality of life scores were similarly affected by OB and placebo. During follow-up, the therapeutic effect of OB remained greater than placebo in terms of withdrawal rate due to symptom relapse (10% vs. 27%, P = 0.009), global efficacy of treatment and relapse-free probability (P = 0.038). Conclusions This placebo-controlled double-blind study shows that otilonium bromide is safe, well tolerated and superior to placebo in reducing the frequency of abdominal pain, severity of abdominal bloating and protecting from symptom relapse in IBS. These results further confirm that patients with IBS can improve during and following treatment with otilonium bromide.
Keywords: SYMPTOM SEVERITY; COLONIC MOTILITY; DOUBLE-BLIND; METAANALYSIS; DISORDERS; PATTERNS; 15-WEEK